Analisis Kinerja Keuangan dan Prediksi Kebangkrutan PT Krakatau Steel Tbk Periode 2014-2018 - Intantri Lestari; Endang Hatma Juniwati; Mochamad Edman Syarief (Indonesian Journal of Economics and Management, 2020)
This study was aimed to find out the financial performance and predictions of bankruptcy of the company Krakatau Steel Tbk. The subjects of this study were the financial statements of PT Krakatau Steel Tbk from 2014-2018 with the descriptive approach method with the Altman Z-score. The data were analyzed statistically used Microsoft Excel. The results of this study over a 5 year period showed results (30 <TS ≤ 40) at the health level, which means that the company is in a "B" or less healthy state. If the performance results are in an unhealthy condition, bankruptcy prediction is carried out. In this case, the prediction value of bankruptcy gets a score of <1.81, the condition is distress zone. It can be concluded that this study shows that financial performance is in an unhealthy condition and the company has the potential to go bankrupt.